Association of Phlebotomy on Blood Product Transfusion Requirements During Liver Transplantation: An Observational Cohort Study on 1000 Cases. Issue 4 (25th March 2022) - Massicotte, Luc; Hevesi, Zoltan; Zaouter, Cédrick; Thibeault, Lynda; Karakiewicz, Pierre; Roy, Louise; Roy, André
Abstract : Background: During the past 2 decades, transfusion requirements have decreased drastically during orthotopic liver transplantation (OLT), and transfusion-free transplantation is nowadays increasingly common. Understanding that liberal intravenous volume loading in cirrhotic patients may have detrimental consequences is key. In contrast, phlebotomy is a method to lower central venous pressure and portal venous pressure. The objective of this study was to determine the effectiveness and safety of phlebotomy in the early phase of blood transfusion, blood loss, renal function, and mortality. Methods: The present study evaluated the impact of phlebotomy on bleeding, transfusion rate, renal dysfunction, and mortality in 1000 consecutive OLTs. Two groups were defined and compared using phlebotomy. Multivariate logistic and linear regression models were used to determine predictors of bleeding, red blood cell (RBC) transfusion, renal dysfunction, and mortality. Results: A mean of 0.7 ± 1.5 RBC units was transfused per patient for 1000 OLTs, 75% did not receive any RBCs, and the median and interquartile range (25–75) were 0 for all blood products transfused. The phlebotomy was associated with decreased transfusion (RBCs, plasma, platelets, cryoprecipitate, albumin), with less bleeding, and with an increased survival rate, both 1 mo and 1 y. Phlebotomy was not associated with renal dysfunction. Conclusions: The practice of phlebotomy to lower portal venous pressure was associated with reduced blood product transfusions and blood loss during liver dissection without deleterious effect on renal function.